Avaliação da permeabilidade intestinal em pacientes com cadiopatia chagásica crônica - Angela Braga Rodrigues (2018)
After more than a century of its original discovery, Chagas disease continues to inflict a heavy burden upon humanity. Around 6 million people are still infected in Latin America, and recently due to globalization, Chagas has become a world heath problem. Of the individuals infected around 30% will have involvement of the heart, and 15% will develop the more severe left ventricular dysfunction, which is its most important prognostic marker. Chagas heart disease is not that different from the other forms of heart failure, regarding hemodynamic and neurohormonal abnormalities. Recently, the gut role in the pathogenesis of heart failure has received more attention from the scientific community. Heart failure is now regarded as a multisystemic disease and as a state of chronic low grade inflammation. There is a hypothesis that under conditions of low cardiac output, there would be epithelial intestinal dysfunction, allowing bacteria and its product translocation, which would activate inflammatory cytokines and worsen heart failure. Our aim was to analyze intestinal permeability abnormalities and compare it to hemodynamic parameters, clinical signs and symptoms, neurohormonal and inflammatory markers and the outcome of Chagas heart disease. We enrolled a group of 50 Chagas heart disease patients and a group of 27 healthy individuals as control. The intestinal permeability test is based on the urinary recovery of two sugar probes, mannitol and lacutlose, that are orally ingested. Patients who had worse left ventricular systolic dysfunction, more pronounced clinical signs of systemic congestion and those with a worse outcome, had reduced levels of urinary excretion rate of mannitol, when compared to the control group. The was no differenced of urinary excretion rate of lactulose and urinary excretion rate of lactulose/mannitol regarding the variables analyzed. Therefore, the present study has suggested an association of the severity of heart failure and urinary reduced levels of mannitol recovery.